Pemetaan Hoaks Keagamaan di Media (Studi Pada Rubrik Cek Fakta Liputan6.com dan Suara.com) - R.S., Nurkarimah Qodarotin; Rachmawati, Farida (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
This article will discuss the mapping of religious hoaxes. The prevalence of fake news has reinforced the responsibility of the media to provide good content to their readers. One form of liability: Online media verify fact-checking columns. This study aims to identify a mapping of religious hoaxes that can serve as a basis for the process of predicting and managing hoaxes. Using content analysis, content types, dis/misinformation types, tools, channels, objects, and clarification models will be mapped As a result, mapping religious hoaxes in liputan6.com and suara.com includes: video is one of the tools that are widely used to manipulate information. The highest dissemination channel is through Facebook social media. The most common types of hoaxes are misleading content and false context.